1993
DOI: 10.1213/00000539-199312000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Positive End-Expiratory Pressure Ventilation Decreases Plasma Atrial and Brain Natriuretic Peptide Levels in Humans

Abstract: To investigate the possible role of atrial and brain natriuretic peptides (ANP and BNP) in the renal effects of mechanical ventilation with positive end-expiratory pressure (PEEP), we measured changes in plasma ANP and BNP levels during PEEP in patients undergoing subtotal esophagectomy. Application of 15 cm of H2O PEEP for 1 h decreased the levels of plasma ANP and BNP from 24.4 +/- 5.5 (mean +/- SEM) and 19.0 +/- 3.5 fmol/mL to 14.4 +/- 2.1 and 15.3 +/- 3.0 fmol/mL, respectively (P < 0.05). The level of plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
7
1
1
Order By: Relevance
“…Many experimental and clinical studies have demonstrated that the decrease in urine output induced by PEEP is mediated in part by a decrease in the secretion of α-ANP, secondary to a reduction in the atrial transmural pressure. 2 In contrast, as shown in the present study, HFJV increased the plasma α-ANP concentration and the urine output.…”
Section: Résultats : Aucune Différence Intergroupe Significative N'a contrasting
confidence: 50%
See 1 more Smart Citation
“…Many experimental and clinical studies have demonstrated that the decrease in urine output induced by PEEP is mediated in part by a decrease in the secretion of α-ANP, secondary to a reduction in the atrial transmural pressure. 2 In contrast, as shown in the present study, HFJV increased the plasma α-ANP concentration and the urine output.…”
Section: Résultats : Aucune Différence Intergroupe Significative N'a contrasting
confidence: 50%
“…1 Recent studies have suggested that a decrease in the plasma ANP concentration contributes to the renal effects of controlled mechanical ventilation (CMV) with positive end-expiratory pressure (PEEP). [2][3][4] On the other hand, the authors have observed that polyuria has often been observed during high frequency jet ventilation (HFJV). However, little is known about the effects of HFJV on the plasma concentration of ANP and renal function.…”
mentioning
confidence: 99%
“…However, elevated BNP appears to lack validity as a biomarker of myocardial dysfunction in sepsis. Potential explanations include inflammation [38], altered clearance [57], altered intrathoracic pressures/mechanical ventilation [58], vasoactive and inotropic drugs [37], fluid management [36,59], and diastolic dysfunction [40]. …”
Section: Discussionmentioning
confidence: 99%
“…extremely high BNP concentrations have been reported in septic patients, even in the presence of preserved left ventricular systolic function 20 . The precise cause of this is unclear but may be due to several potential confounders, including inflammation 21,22 , impaired clearance 5 and commonly employed therapies such as altered intrathoracic pressures/ mechanical ventilation 23 and the use of vasoactive and inotropic drugs 24 . In keeping with previous data, static values of CVP did not predict haemodynamic response to fluid challenge 7 .…”
Section: Discussionmentioning
confidence: 99%